2018
DOI: 10.1007/s10067-018-4260-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-6 and interleukin-10 expression, gene polymorphisms, and Takayasu arteritis in a Chinese Han population

Abstract: Takayasu arteritis (TA) is a chronic inflammatory disease. Interleukin (IL)-6 and IL-10 are important cytokines involved in the immune response of TA in some ethnicities. We investigated whether the single-nucleotide polymorphism (SNP) of IL-6 and IL-10 genes and their expressions were associated with TA in a Chinese Han population. One hundred eighty-four TA patients and 235 healthy controls (HC) were recruited. DNA and RNA were extracted from peripheral blood cells. Genotyping of IL-6 and -10 was performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…It was significantly reduced in active patients compared with stable patients, and higher IL-10 levels was correlated with a long-term remission of TAK. 26 , 27 In the present study, there was no significant difference in serum IL-10 levels between TAK patients at baseline and healthy controls. However, after 6 months of GCs and TOF treatment, IL-10 was significantly increased in TAK patients, indicating that GCs and TOF could enhance the anti-inflammatory responses.…”
Section: Discussioncontrasting
confidence: 44%
“…It was significantly reduced in active patients compared with stable patients, and higher IL-10 levels was correlated with a long-term remission of TAK. 26 , 27 In the present study, there was no significant difference in serum IL-10 levels between TAK patients at baseline and healthy controls. However, after 6 months of GCs and TOF treatment, IL-10 was significantly increased in TAK patients, indicating that GCs and TOF could enhance the anti-inflammatory responses.…”
Section: Discussioncontrasting
confidence: 44%
“…Two studies reported rs1800871 polymorphism and TAK, 14,15 while no significant relationship was found, which were T vs t: 1.22 (95% CI: 0.90, 1.64, I 2 = 0%); TT vs tt: 1.48 (95% CI: 0.78, 2.80, I 2 = 0%); Tt vs tt: 1.44 (0.89, 2.35, I 2 = 0%); TT + Tt vs tt: 1.44 (95% CI: 0.90, 2.29, I 2 = 0%); and TT vs TT + Tt: 1.16 (95% CI: 0.67, 2.01, I 2 = 0%) (all P > 0.05, Figure 3). Three reported rs1800872 polymorphism, 5,14,15 yet no significant relationship was found, which were T vs t: 0.97 (95% CI: 0.79, 1.20, I 2 = 0%); TT vs tt: 0.94 (95% CI: 0.59, 1.50, I 2 = 0%); Tt vs tt: 1.22 (95% CI: 0.83, 1.79, I 2 = 0%); TT + Tt vs tt: 1.39 (95% CI: 0.95, 2.03, I 2 = 55%); and TT vs TT + Tt: 0.86 (95% CI: 0.62, 1.19, I 2 = 0%) (all P > 0.05, Figure 4). Two reported rs1800896 polymorphism, 14,15 also, no significant relationship was found, which were T vs t: 1.11 (95% CI: 0.77, 1.58, I 2 = 34%); TT vs tt: 1.15 (95% CI: 0.40, 3.28, I 2 = 0%); Tt vs tt: 0.99 (95% CI: 0.34, 2.90, I 2 = 0%); TT + Tt vs tt: 1.11 (95% CI: 0.39, 3.13, I 2 = 0%); and TT vs TT + Tt: 1.11 (95% CI: 0.72, 1.70, I 2 = 56%) (all P > 0.05, Figure 5).…”
Section: Resultsmentioning
confidence: 91%
“…After this preliminary screening, 17 studies were selected through screening the full text. According to the inclusion and exclusion criteria, 7 studies were eventually selected for the meta-analysis 5,[12][13][14][15][16][17] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we found that when comparing the active TAK patients to the inactive TAK patients, although there were increased mRNA levels of TCR, CD28, GATA3, RORC, and FOXP3, which indicate that T cells were involved in the disease activity of TAK, these mRNA levels of many immune checkpoints were not increased, such as CTLA4, PD-1, LAG3, TIGIT, and TIM3. We speculate that it might be related to the attenuated secretion of IL-10 in PBMCs of TAK patients [ 32 , 41 43 ]. Notably, although these immune checkpoints were not increased in active stage than in inactive stage, the emerging gene co-expression revealed the activation of these immune checkpoints in active TAK stage, which suggests that gene co-expression network might more accurately reflect the activation of T cells than the gene expression levels in TAK.…”
Section: Discussionmentioning
confidence: 99%